Papua New Guinea : Fourth Review Under the Stand-By Arrangement and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2001)
Despite difficult political and economic circumstances, Papua New Guinea has made progress toward stabilization and structural reform under the program supported by the Stand-By Arrangement. Executive Directors welcomed these developments, and stressed the need to maintain fiscal and monetary stances, and accelerate structural reforms. They cautioned the authorities to remain vigilant over financial developments and implement additional corrective actions, if needed. They agreed that the country has completed the fourth review under the Stand-by Arrangement, and approved a waiver.